PENGARUH KOMBINASI PIGMEN KURKUMIN-Î²-KAROTEN TERHADAP SPEKTRA ABSORPSI DAN NILAI SPF PADA SEDIAAN LOTION - Yanti, Ninda Meili; Alimuddin, Andi Hairil; Rahmalia, Winda (Tanjungpura University, 2024)
This research aimed to examine the effect of the combined use of curcumin and Î²-carotene pigments on their absorption spectra. Subsequently, these pigment combinations were incorporated into a lotion formulation to determine their respective Sun Protection Factor (SPF) values. Mixtures of curcumin and Î²-carotene were prepared at mass ratios (w/w) of 0:5, 1:4, 2:3, 3:2, 4:1, and 5:0. Their absorption spectra were analyzed with a UV-Vis spectrophotometer over the 200